Spatial synergies between auditory and visual attention - Driver, J; Spence, C (MIT Press, 1994)
Three experiments examined spatial links between endogenous attention in vision and audition. In Experiment 1 subjects were presented auditorily with two verbal messages, one from either side of their midline. They had to repeat one message, for which they were also given lip-read information in some conditions. The lip-read information produced a larger improvement in performance when presented on the same side as the target sounds rather than the opposite side, suggesting a difficulty in attending to different locations in the two modalities. This difficulty cannot be attributed to the direction of gaze, as there was no effect of passively fixating meaningless lip-movements on the same versus opposite side as the target sounds. A similar (albeit reduced) difficulty in attending to different locations in the two modalities was observed in Experiment 2, where the auditory and visual tasks were unrelated. The auditory task was shadowing as before, while the visual task was monitoring for a specified target in a stream of visual characters appearing successively at a single location. A decrement in shadowing was observed when the monitored visual events were in a different location to the target sounds. Again, there was no effect of the direction of passive fixation. A final experiment found that the cost of attending to different locations in the two modalities can be observed in the conventional dual-task situation, i.e. with no distractor stimuli. These results demonstrate synergetic links between endogenous spatial attention in vision and audition.